High-Resolution Melting Analysis as an Appropriate Method to Differentiate between Fasciola hepatica and F. gigantica - Ahmad HOSSEINI-SAFA; Mohammad Bagher ROKNI; Sayed Hussain MOSAWI; Peyman HEYDARIAN; Hakim AZIZI; Afshin DAVARI; Mojgan ARYAIEPOUR (Tehran University of Medical Sciences, 2019)
Background: Fasciolosis is a shared disease between humans and livestock caused by hepatic trematodes; Fasciola hepatica and F. gigantica. Differentiate between the two species of this genus is essential. High-Resolution Melting (HRM) Analysis represents a new approach to this issue. This method can be performed right after termination of Real-Time PCR. This technique has not been used for identification of adult F. hepatica and F. gigantica genotypes. The aim of this study was to determine Fasciola species by using HRM in isolates taken from Iran, respectively. Methods: Ninety-three Fasciola spp. samples were collected from infected slaughtered animals in different regions of Iran, including North West (Ardebil Province) and South East (Zahedan Province) during 2016. Genomic DNA from the samples was extracted using a DNA extraction kit and then after Real-Time PCR amplification, HRM was done. Results: Overall, 59 and 34 isolates were identified as F. hepatica and F. gigantica, respectively. The percentages of each species from animals were as follows: sheep (F. hepatica, 80.39% and F. gigantica, 19.61%), cattle (F. hepatica, 42.85% and F. gigantica, 57.15%). Conclusion: HRM technique developed in the present study is a powerful, rapid and sensitive technique for epidemiological survey and molecular identification between F. hepatica and F. gigantica.